Intergenerational Analysis of Patronymic Transformations in the Quebec (Canada) Population Since the Seventeenth Century. (2nd January 2017) - Tremblay, Marc
Abstract : Surnames may undergo several transformations over time. Thus, patronymic distributions observed in a population at a given time may hide changes that occurred previously, the extent of which can be estimated with intergenerational data. Using a corpus of 5, 100 deep-rooted ascending genealogies from the Quebec (Canada) population, this study compares contemporary surnames with those of founding ancestors in each paternal line and identifies various patronymic mutations occurring over multiple generations. On average, paternal lines go back eight generations. About one-third of all paternal lines presented at least one orthographic difference between the contemporary and the original surnames. Many surnames were transformed several times in a single paternal line, and some changes were different for a given surname along different lines. Most changes occurred among the first generations following that of the founding ancestors. Regional comparisons also show important variations.